2009
DOI: 10.1057/ejdr.2008.7
|View full text |Cite
|
Sign up to set email alerts
|

International development and the ‘perpetual present’: Anthropological approaches to the re-historicization of policy

Abstract: Development agencies tend to focus more strongly on the promised delivery of change in the future than they do on analysing the historical contexts and origins of development ideas and practices. The histories of development ideas and agencies, as well as those of the people who work within them, are therefore important topics for anthropological attention. This paper sets out arguments for an anthropological approach that contributes a renewed sense of history to development policy and practice. There are two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 17 publications
2
24
0
1
Order By: Relevance
“…This kind of finding is supported by Rahman (2006), White (1999), Lewis (2004, 2009) and Islam and Morgan (2012b). We found that there was little consultative participation of the blacksmiths and goldsmiths.…”
Section: Discussionsupporting
confidence: 84%
“…This kind of finding is supported by Rahman (2006), White (1999), Lewis (2004, 2009) and Islam and Morgan (2012b). We found that there was little consultative participation of the blacksmiths and goldsmiths.…”
Section: Discussionsupporting
confidence: 84%
“…6 Elman and Elman (2001) is a similar exercise seeking to connect historians and political scientists studying international relations, but with less emphasis on the implications for policy; see also McDonald (1996) and Sewell (2005) on links between historians and sociology. Most recently, see Lewis (2009), who correctly argues that '[t]he lack of historical perspective with development agencies stems partly from the pressures of development work in which activities remain powerfully History, historians and development policy…”
Section: Notesmentioning
confidence: 99%
“…Anthropologists have pointed out that humanitarian and development aid work tends to operate on either “a radical insistence on the present” (Redfield :200) or “the promise of generating future change” (Lewis :42). That is, in the moment of humanitarian emergency or in the aspirations for “progress,” the past tends to become eclipsed in both aid activities and analyses of them (cf.…”
Section: The (Japanese) Past As a Resource For International Aidmentioning
confidence: 99%